Digital Transformation Planning Based on Big Data Technology (Case Study: XYZ Bank) - Raya Agung Astri Wardhani; Gunawan Wang (Jurnal Manajemen Informatika (JAMIKA), 2022)
Bank XYZ is one of the regional government-owned banks which as of August 16, 2021 has a total percentage of customers who have dormant accounts reached 50.43%. This happens because currently the development of the marketing strategy used by Bank XYZ is still based on the products and services owned by Bank XYZ, not referring to customer needs. For this reason, the purpose of this research is to make a digital transformation plan that can be used by Bank XYZ in order to become a customer-centric bank using Big Data technology. The method used to carry out this research is to use the Big Data Framework for Agile Business (BDFAB). The results of this study includes mapping data requirements and Big Data technology for Bank XYZ, the impact to business processes, proposals for changes in information system architecture, planning for quality control mechanisms, to changes in organizational structure so that the benefits obtained by Bank XYZ are a more personalized marketing approach to customers, increased accuracy in offering bank products and services based on customer profiles, needs, behavior, and interests, as well as increased customer engagement and customer satisfaction.